2021
DOI: 10.3390/antiox10081265
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Curcumin Improves Energy Metabolism, Brain Monoamines, Carcass Traits, Muscle Oxidative Stability and Fatty Acid Profile in Heat-Stressed Broiler Chickens

Abstract: The aim of the present study was to elucidate the impacts of dietary curcumin supplementation on energy metabolism, brain monoamines and muscle oxidative stability in heat-stressed broilers. In total, 120 day-old chicks were allocated into three equal groups of four replicates. The first group (T1) was maintained on a thermoneutral condition, while the second group (T2) was subjected to 8 h of thermal stress (34 °C), and both groups fed the basal diet with no supplement. The third group (T3) was exposed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…Curcumin can have significant effects, such as antioxidant and anti‐inflammatory effects (Liu et al, 2020). Dietary turmeric powder supplementation improved the performance and antioxidant capacity of heat‐stressed broiler chickens (Salah et al, 2021). Many investigators have studied the effect of turmeric powder and essential oil and their active components on livestock and indicated that turmeric has the potential to increase digestive enzymes activities, improve liver integrity, and decrease serum cholesterol level (Gandhi et al, 2011; Platel & Srinivasan, 2000; Van Phuoc et al, 2019) that can be beneficial to improve performance and egg quality of laying hens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin can have significant effects, such as antioxidant and anti‐inflammatory effects (Liu et al, 2020). Dietary turmeric powder supplementation improved the performance and antioxidant capacity of heat‐stressed broiler chickens (Salah et al, 2021). Many investigators have studied the effect of turmeric powder and essential oil and their active components on livestock and indicated that turmeric has the potential to increase digestive enzymes activities, improve liver integrity, and decrease serum cholesterol level (Gandhi et al, 2011; Platel & Srinivasan, 2000; Van Phuoc et al, 2019) that can be beneficial to improve performance and egg quality of laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin can have significant effects, such as antioxidant and anti-inflammatory effects (Liu et al, 2020). Dietary turmeric powder supplementation improved the performance and antioxidant capacity of heat-stressed broiler chickens (Salah et al, 2021).…”
mentioning
confidence: 99%
“…These above results indicated that CUR was effective in reducing coccidia infection in poultry through its antioxidant and antimicrobial properties, indicating that CUR alone or cotreatment with other feed additives could be recommended as a strategy to improve gut health in broilers [ 58 ]. In heat-stressed broilers, Ayman et al [ 70 ] elucidated the impacts of dietary CUR supplementation on energy metabolism, brain monoamines and muscle oxidative stability. The results showed that compared with heat-stressed broilers, increased breast yield and reduced abdominal fat mass were observed in CUR supplemented broilers.…”
Section: Resultsmentioning
confidence: 99%
“…The diet-microbiome interaction is based on the action of metabolites and nutritional components derived from the diet on the host organ systems. Salah et al [ 80 ] experimented on chicken broilers exposed to heat stress (8 h, 34 °C) and fed a diet supplemented with curcumin (100 mg/kg diet). These studies showed that the addition of curcumin to a diet of heat stressed-chickens doubled the level of coenzyme Q10 in the liver [ 80 ].…”
Section: Factors Affecting the Gut-liver-brain Axis In Poultrymentioning
confidence: 99%